Minimising drag coefficient of a hatchback car utilising fractional factorial design algorithm. Issue 4 (4th July 2018) - Vahdati, Mehrdad; Beigmoradi, Sajjad; Batooei, Alireza
ABSTRACT: Aerodynamic force is known as one of the most important attributes, which has significant weight on fuel consumption and vehicle performance. In this paper, minimising drag coefficient is performed considering modification of rear end factors. To this end, five geometrical parameters of a hatchback car are chosen as design factors in two levels: (1) rear spoiler length, (2) rear spoiler angle, (3) rear diffuser angle, (4) boat tail angle (5) fifth door height. Main and interaction effects of these factors on drag coefficient are investigated using design of experiments and optimum level for each parameter is achieved. Computational fluid dynamic method is applied to evaluate air stream around the car. To reduce the number of simulations fraction, factorial design algorithm is applied which decreased the number of case studies to half. Characteristics of airflow around optimum car model are discussed and reported at the end.